2009
DOI: 10.1128/mcb.00224-09
|View full text |Cite
|
Sign up to set email alerts
|

Alpha Interferon Induces Long-Lasting Refractoriness of JAK-STAT Signaling in the Mouse Liver through Induction of USP18/UBP43

Abstract: Recombinant alpha interferon (IFN-␣) is used for the treatment of viral hepatitis and some forms of cancer. During these therapies IFN-␣ is injected once daily or every second day for several months. Recently, the long-acting pegylated IFN-␣ (pegIFN-␣) has replaced standard IFN-␣ in therapies of chronic hepatitis C because it is more effective, supposedly by inducing a long-lasting activation of IFN signaling pathways. IFN signaling in cultured cells, however, becomes refractory within hours, and little is kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 58 publications
9
147
1
1
Order By: Relevance
“…5,6,29 However, although SOCS-3 has been reportedly elevated in the liver of chronic hepatitis C patients with IR, 7 its role in reducing the response to therapy has been challenged by experimental 30 and clinical data. 31 A second hypothesis is based on data suggesting that high concentrations of insulin directly inhibit interferon alpha signaling, independently of SOCS-3.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,29 However, although SOCS-3 has been reportedly elevated in the liver of chronic hepatitis C patients with IR, 7 its role in reducing the response to therapy has been challenged by experimental 30 and clinical data. 31 A second hypothesis is based on data suggesting that high concentrations of insulin directly inhibit interferon alpha signaling, independently of SOCS-3.…”
Section: Discussionmentioning
confidence: 99%
“…USP18 has been reported to be responsible for the persistent IFN-induced refractory mechanism that occurs following JAK-STAT signalling in mouse and human hepatocytes (Francois-Newton et al, 2011;Sarasin-Filipowicz et al, 2009). The microarray data showed that IFN-l4 induced strong USP18 expression (Fig.…”
Section: Ifn-l4 Induces Long-term Usp18 Expressionmentioning
confidence: 99%
“…Ubiquitin specific peptidase 18 (USP18), also known as ubiquitin-specific protease 43 (UBP43), provides strong negative feedback in the activation of the JAK-STAT pathway by binding to IFNAR2 (Sarasin-Filipowicz et al, 2009). USP18 has been reported to be responsible for the persistent IFN-induced refractory mechanism that occurs following JAK-STAT signalling in mouse and human hepatocytes (Francois-Newton et al, 2011;Sarasin-Filipowicz et al, 2009).…”
Section: Ifn-l4 Induces Long-term Usp18 Expressionmentioning
confidence: 99%
“…Therefore, host cells develop stringent mechanisms of signal attenuation, for example, termination of IFN signaling, to ensure an appropriate IFN response (Ivashkiv and Donlin, 2014;Schneider et al, 2014). Among the inhibitors, USP18 (ubiquitinspecific protease) impedes the expression of IFN-induced downstream genes by negative regulation of Jak-Stat signaling pathway Malakhova et al, 2003;Sarasin-Filipowicz et al, 2009;Schneider et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed USP18-deleted mice are hypersensitive to IFN treatment and show enhanced resistance to viral infection (Malakhova et al, 2003;Ritchie and Zhang, 2004); USP18−/− cells treated with type I IFNs have enhanced and prolonged STAT1 phosphorylation, increased the expression of ISG (Malakhova et al, 2003;Murray et al, 2011;Sarasin-Filipowicz et al, 2009). Interestingly, USP18 is a major ISG15-specific protease for maintaining a proper balance of ISG15-conjugated proteins in cells; however, the antiviral roles of USP18 are independent of its ISG15 isopeptidase activity Malakhova et al, 2006;Osiak et al, 2005), and seem to be mediated by specific binding of USP18 to the IFN receptor IFNAR2 and subsequently disrupting IFNAR2-JAK1 interaction, thus negatively regulating IFN signaling cascade (Malakhova et al, 2006).…”
Section: Introductionmentioning
confidence: 99%